Anaerobic co-digestion of sodium hydroxide pretreated sugarcane leaves with pig manure and dairy manure - Luo, Juan; Meng, Haibo; Yao, Zonglu; Wachemo, Akiber Chufo; Yuan, Hairong; Zhang, Liang; Li, Xiujin (International Journal of Agricultural and Biological Engineering, 2018)
Sugarcane leaves (SL) pretreated by alkali was used as substrate to enhance biogas production via mesophilic anaerobic digestion (AD) in this study. Effectiveness of different concentrations of NaOH pretreatment on AD performance was investigated. Results showed that compared to untreated sample of SL, the lignocellulose (LCH) content of NaOH pretreated group was decreased by 5.79%-16.85%. However, the cumulative biogas production of the pretreated samples increased in the range of 34.54%-82.67%; moreover, T90 was shorten by 5-7 d. The highest anaerobic digestibility of SL was achieved at 6% NaOH pretreatment, which produced 287.30 mL/g TS of biogas. A significant interactive effect of the three parameters (temperature, SL/manure mixing ratio and C/N ratio) was found on the biogasification of anaerobic co-digestion, and a maximum biogas production was achieved at 36.2oC, mixing ratio of 1.6 and C/N ratio of 29.2. These show that the verification experiment confirmed the optimization results. This study provides meaningful insight for exploring efficient pretreatment strategy and optimal condition to stabilize and enhance AD performance for practical application.Keywords: NaOH pretreatment, co-digestion, sugarcane leaves, pig manure, dairy manureDOI: 10.25165/j.ijabe.20181104.4079Citation: Luo J, Meng H B, Yao Z L, Wachemo A C, Yuan H R, Zhang L, et al. Anaerobic co-digestion of sodium hydroxide pretreated sugarcane leaves with pig manure and dairy manure. Int J Agric & Biol Eng, 2018; 11(4): 224-229.